Oxidation of an Exposed Methionine Instigates the Aggregation of Glyceraldehyde-3-phosphate Dehydrogenase - Samson, Andre L. (American Society for Biochemistry and Molecular Biology, 2014)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a ubiquitous and abundant protein that participates in cellular energy production. GAPDH normally exists in a soluble form; however, following necrosis, GAPDH and numerous other intracellular proteins convert into an insoluble disulfide-cross-linked state via the process of “nucleocytoplasmic coagulation.” Here, free radical-induced aggregation of GAPDH was studied as an in vitro model of nucleocytoplasmic coagulation. Despite the fact that disulfide cross-linking is a prominent feature of GAPDH aggregation, our data show that it is not a primary rate-determining step. To identify the true instigating event of GAPDH misfolding, we mapped the post-translational modifications that arise during its aggregation. Solvent accessibility and energy calculations of the mapped modifications within the context of the high resolution native GAPDH structure suggested that oxidation of methionine 46 may instigate aggregation. We confirmed this by mutating methionine 46 to leucine, which rendered GAPDH highly resistant to free radical-induced aggregation. Molecular dynamics simulations suggest that oxidation of methionine 46 triggers a local increase in the conformational plasticity of GAPDH that likely promotes further oxidation and eventual aggregation. Hence, methionine 46 represents a “linchpin” whereby its oxidation is a primary event permissive for the subsequent misfolding, aggregation, and disulfide cross-linking of GAPDH. A critical role for linchpin residues in nucleocytoplasmic coagulation and other forms of free radical-induced protein misfolding should now be investigated. Furthermore, because disulfide-cross-linked aggregates of GAPDH arise in many disorders and because methionine 46 is irrelevant to native GAPDH function, mutation of methionine 46 in models of disease should allow the unequivocal assessment of whether GAPDH aggregation influences disease progression.